William Ludlam: portrait of an eighteenth-century mathematician - Decesare, Richard (Bshm Bulletin: Journal of The British Society for The History of Mathematics, 2011)
In 1785, William Ludlam wrote a book entitled The rudiments of mathematics. After I purchased the 1790 edition of this text some years ago at an antiquarian bookstore in Connecticut, I became interested in learning more about him. Ludlam's name had appeared as a footnote in several histories of mathematics, but little else had been written about him. I began some research, simply out of curiosity. What emerged was a story of an interesting mathematician, scientist, inventor, and clergyman - and a man who often found himself in the middle of controversy and subject to personal attacks, whether deserved or not. This article is a biography of Ludlam, in which I have used his own words, as well as those of his adversaries, wherever possible. © 2011 British Society for the History of Mathematics.
Keywords: dept.mat